2022
DOI: 10.1088/1361-6668/ac9932
|View full text |Cite
|
Sign up to set email alerts
|

3D homogenization of the T-A formulation for the analysis of coils with complex geometries

Abstract: The modeling and analysis of superconducting coils is an essential task in the design stage of most devices based on high-temperature superconductors (HTS). These calculations allow verifying basic estimations and assumptions, proposing improvements, and computing quantities that are not easy to calculate with an analytical approach. For instance, the estimation of losses in HTS is fundamental during the design stage since losses can strongly influence the cooling system requirements and operating temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…In addition, Neumann boundary conditions are applied to the internal and external surfaces to fulfil the definition as [12], [22]:…”
Section: B 3d T-a Homogenization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Neumann boundary conditions are applied to the internal and external surfaces to fulfil the definition as [12], [22]:…”
Section: B 3d T-a Homogenization Methodsmentioning
confidence: 99%
“…More recently, in our previous work [9], we carried out AC loss simulations on HTS coil windings coupled with an iron core using the 3D T-A homogenization method [10]- [12]. Results showed that the AC loss in the 8DPC (double pancake coil) Manuscript received November 10, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, several numerical approaches have been proposed to investigate the electromagnetic behavior of HTS devices, for instance, A − V formulation [52,53], H − ϕ formulation [54], H formulation [55,56], and T − A formulation [57,58]. Among them, the T − A formulation has become one of the most popular methods in the field of HTS numerical simulation, which has been used in the electromagnetic calculation of the racetrack coil [59,60]. The T − A formulation is easily implemented in the commercial finite element software package COMSOL Multiphysics [61], which effectively reduces the difficulty of numerical modeling of superconductors.…”
Section: Electromagnetic Modeling Of 3d Hts Racetrack Coilmentioning
confidence: 99%
“…To reduce the computation burden of the 3D model, the homogenization technique is adopted to simplify the numerical model [65]. Additionally, the Neumann boundary condition should be applied to the other two boundaries of homogeneous bulk [60,65],…”
Section: Electromagnetic Modeling Of 3d Hts Racetrack Coilmentioning
confidence: 99%
“…Due to the adoption of the thin-band approximation, its convergence and computational efficiency have been improved and it is suitable for superconducting structures with extremely high aspect ratios. In addition, it can complete electromagnetic field calculations of 3D superconducting magnet models with complex geometric structures combined with curved coordinate systems [20].…”
Section: Introducementioning
confidence: 99%